Perbandingan Sistem Gadai Konvensional Dan Gadai Syariah Perspektif Ekonomi Islam - Nilam Erman (EL-EMIR Institute, 2026)
The development of financial institutions in Indonesia has led to the emergence of various financing systems, including conventional pawning and Sharia pawning. This research is important due to the low public understanding of the differences between the two systems, especially from an Islamic economic perspective. The purpose of this study is to analyze the comparison between conventional pawning and Sharia pawning systems and to identify their advantages and disadvantages in practice. This research uses a qualitative approach with a literature review. Data were obtained from books, scientific journals, fatwas from the National Sharia Council (DSN-MUI), academic articles, and other sources relevant to the research topic. Data analysis used a descriptive-comparative method, comparing aspects of the contract, transaction mechanism, and profit system of the two types of pawning. The results show that Sharia pawning is more in line with Islamic economic principles because it uses the rahn and ijarah contracts and is free from riba (usury). Meanwhile, conventional pawning still employs an interest system, which is considered riba in Islam. Sharia pawning is also considered fairer, more transparent, and emphasizes the principle of mutual assistance in economic transactions.